Therapeutic Potential of Quercetin and their Compound Against Ovarian Cancer: New Approaches & Application - Duraipandian, M.; Elumalai, K.; Chole, Pranjali Bajrang; Ambika, J.; Gajendhini, S.; Kesavapriya, N.; Geetha, M.; Naaz, Farha (Journal for Research in Applied Sciences and Biotechnology, 2024)
Ovarian cancer is an exceptionally perilous form of cancer as it develops within the female reproductive system. Finding effective therapy platforms for ovarian cancer has been difficult because to the diverse array of molecular pathways and genetic alterations involved in its development. Therefore, it is imperative to discover novel therapeutic methodologies and advance their development. Medicinal herbs possess the capacity to independently or in combination with other pharmaceuticals, effectively treat malignancies such as ovarian cancer. Quercetin possesses remarkable anti-inflammatory and anti-cancer properties, making it one among numerous natural compounds with such qualities. Quercetin has demonstrated cytotoxicity against ovarian cancer cells in both laboratory experiments (in vitro) and live animal tests (in vivo). The potential anti-cancer effects of quercetin, particularly in relation to ovarian cancer, have not been extensively studied in human trials, despite encouraging findings from laboratory and animal experiments. Hence, it seems that quercetin could potentially be utilized in clinical trials as a therapeutic agent, either on its own or in conjunction with other chemotherapeutic drugs. This article will outline the primary aspects of quercetin's anti-cancer characteristics and thereafter concentrate on its application in the treatment of ovarian cancer.